Clinical Recommendations on Managing Seborrheic Dermatitis in Children - E. I. Pilguy; N. N. Murashkin (Педиатрическая фармакология)
Seborrheic dermatitis is a widespread erythematous/squamous disease associated with high secretory activity of sebaceous glands. This article presents epidemiological characteristics of the disease and ethiopathogenetic mechanisms of the process. Given high prevalence of the disease, we present clinical pictures of the pediatric and adult forms of the disease, detailed differential/diagnostic algorithm and contemporary recommendations on pharmacological treatment and follow-up management of patients with seborrheic dermatitis.